KOORDINASI PEMERINTAH DALAM PEMANFAATAN SMART CARD MADANI TAHUN 2019-2020 (STUDI PADA DINAS KOMUNIKASI, INFORMATIKA, STATISTIK, DAN PERSANDIAN KOTA PEKANBARU) - Deva, Muhammad Haffiza Yusilfa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The Madani Smart Card innovation is part of the Pekanbaru City Government's efforts to support the implementation of the Electronic-Based Government System (SPBE), in order to meet public demands for easy yet high-quality administrative services. This study aims to analyze the effectiveness of coordination carried out by the Pekanbaru City Communication, Informatics, Statistics and Cryptography Agency in implementing the Madani Smart Card during the 2019–2020 period. The Madani Smart Card was developed as an information technology-based public service innovation in order to support the implementation of smart cities. Four Regional Apparatus Organizations (OPDs) were the primary targets for implementation: the Communication, Informatics, Statistics and Cryptography Agency, the Education Agency, the Health Agency, and the Transportation Agency. The Communication, Informatics, Statistics and Cryptography Agency pioneered the use of this card as an electronic attendance tool for all employees and casual workers. This success earned the Agency Head an award as one of the Top 3 Exemplary Pratama High-Level Officials (PPT) at the 2019 ASN Awards from the Ministry of Administrative and Bureaucratic Reform. The method used was a qualitative descriptive approach, with data collection techniques through interviews, observation, and documentation. The results indicate that coordination has been quite effective, although challenges remain, including cross-OPD integration, varying technical readiness, and limited human resources. This study recommends increasing synergy between OPDs and strengthening digital infrastructure to optimize the sustainable use of the Madani Smart Card. Keywords: Government coordination, Smart Card Madani, Electronic-Based Government System, Effectiveness, Information technology.